SCREENING FOR β -THALASSEMIA TRAIT OR OTHER HEMOGLOBINOPATHIES IN FAMILIES OF THALASSEMIA MAJOR PATIENTS - Maliha Asif; Sabeen Fatima; Yasmeen Batool; Nidda ayub; Nusrat Alavi; Ali Raza; Bakhtawar Farooq; Aftab Hussain; Ubaid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: Screening of extended families including first degree relative of Thalassemia major children for the presence of β Thalassemia minor or other hemoglobinopathies Study Design: Cross-sectional descriptive study. Setting: Punjab Thalassemia Prevention Program, Nishtar Hospital Multan. Period: Six months,1st October 2023 to 1st April 2024. Material and Methods: CBC’s and peripheral smears of 11310 first degree relatives from 138 families with index case of thalassemia major, were done. Those (7299) with MCV and MCH less than 75fl and 25pg respectively and had microcytic hypochromic blood picture on peripheral smear, were included in the study. Their 2cc blood sample was taken for Hb electrophoresis. Those whose Hb A2 levels came out to be > 3.5% were labelled as beta thalassemia carriers, those with HbA2 levels 3.0-3.4% were considered inconclusive/ borderline and their serum ferritin levels were done to screen IDA. If they were iron deficient, they were given iron supplements for six month and Hb electrophoresis was repeated after 6 months. Results: Out of 7299 extended family members of beta thalassemia major patients.26.67% were beta thalassemia carriers (beta thalassemia trait), 68.78% were non carrier for beta thalassemia trait, 4.13% were repeat or borderline, while 0.39% have other hemoglobinopathies. Conclusions: In third world countries like us cascade screening seems to be one of the most cost-effective approaches to identify carriers of beta thalassemia.